Sanye Tablet Ameliorates Insulin Resistance and Dysregulated Lipid Metabolism in High-Fat Diet-Induced Obese Mice - Minghe Yao; Minghe Yao; Lin Li; Lin Li; Ming Huang; Ming Huang; Yao Tan; Yao Tan; Ye Shang; Ye Shang; Xianghui Meng; Xianghui Meng; et al. (Frontiers Media S.A., 2021)
Sanye Tablet (SYT) is a patent prescription widely used in treating T2D and pre-diabetes, especially T2D comorbid with hypertriglyceridemia, for many years in China. However, the underlying mechanism that accounts for the anti-diabetic potential of SYT by regulating lipid-related intermediates remains to be elucidated. This study aimed to investigate the mechanism of SYT on lipid metabolism and insulin sensitivity in high-fat diet (HFD)-induced obese mice by means of combining lipidomics and proteomics. The obese mice models were developed via HFD feeding for 20 consecutive weeks. Mice in the treatment group were given metformin and SYT respectively, and the effects of SYT on body weight, blood glucose, insulin sensitivity, fat accumulation in the organs, and pathological changes in the liver were monitored. Lipid metabolism was examined by lipidomics. Further determination of signaling pathways was detected by proteomics. The biological contributions of the compounds detected in SYT's chemical fingerprint were predicted by network pharmacology. SYT treatment reduced body weight, inhibited viscera and hepatic steatosis lipid accumulation, and prevented insulin resistance. Furthermore, it was found that circulatory inflammatory cytokines were reduced by SYT treatment. In addition, lipidomics analysis indicated that SYT targets lipid intermediates, including diacylglycerol (DAG) and Ceramide (Cer). Mechanistically, SYT positively affected these lipid intermediates by suppressing liver lipogenesis via downregulation of SREBP1/ACC and the JAK/STAT signaling pathway. Our results predicted that astragalin and rosmarinic acid might regulate the JAK-STAT pathway by targeting PIM2 and STAT1, respectively, while paeoniflorin and rosmarinic acid were likely to regulate inflammatory responses by targeting TNFα, IL-6, and IL-4 during T2D. Overall, our study provides supportive evidence for the mechanism of SYT's therapeutic effect on dysregulated lipid metabolism in diabesity.